Analyzing the Stressors for Frontline Soldiers Fighting Against Coronavirus Disease 2019 Pandemic - Shaukat, Muhammad Zeeshan; Scholz, Miklas; Qazi, Tehmina Fiaz; Niazi, Abdul Aziz Khan; Basit, Abdul; Mahmood, Asif (Frontiers in Psychology, 2021)
The study aims to analyze stressors to which medical staff is vulnerable due to the COVID-19 pandemic. It also imposes a hierarchy on complex relations among stressors for excavating underlying structure and builds a model of inter-relationships contrasting reality. The design of the study comprises a literature survey, data collection from primary sources and analysis. Stressors have been explored from within current published/unpublished literature and validated by experts through approval vote. Data were collected from the focus group (panel of experts), and Interpretive Structural Modeling (ISM) was used as the research methodology. ISM’s findings are avowed through ‘cross-impact matrix multiplication applied to classification’ (MICMAC analysis). As a result of the literature survey, a list of stressors was generated, and total nineteen stressors qualified as representative of the phenomenon. The results of ISM show that two stressors (i.e. ‘unavailability of proper PPEs’ and ‘lack of proper communication’) emerged as the most critical stressors since they occupy the bottom of the model, whereas, four stressors (i.e. ‘anxious about isolation/quarantine’, ‘subject to violent crimes’, ‘feeling frustrated and powerless’ and ‘exhausting shifts/hours without clear end’) are relatively less critical since they occupy the top of the model. The rest of the stressors occupy the middle of the model, and, therefore, have moderate-severe effects on frontline soldiers. The results of MICMAC show that the stressor ‘subject to violent crimes’ is classified in the dependent cluster, remaining fall in the linkage cluster but no stressor fall in independent & autonomous. Overall results indicate that all stressors are relevant to the phenomenon under study, but they are currently not settled. The study is invaluable for policymakers, frontline soldiers, researchers, the international community and society because it provides a lot of new information that is helpful in refining strategies and combating influential stressors.